2015
DOI: 10.1017/jmo.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Goal orientation and employee creativity: The mediating role of creative role identity

Abstract: We developed and tested a model of employee creativity based on achievement goal theory and role identity theory. Examining the relationship between the three dimensions of goal orientation and employee creativity, we explored the mediating effect of creative role identity. Data were collected from 197 employees and their supervisors from several industries in China. The results indicated that employee learning orientation was positively related to employee creativity, but that no such positive relationship ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 50 publications
(160 reference statements)
3
29
0
Order By: Relevance
“…Our results support this approach, especially in regard to the robustness of our hypothesized effects while controlling for CRI that would be expected to align with gender role identity. However, it is also noteworthy that CRI did not significantly correlate with gender in our sample, a curious but not unprecedented finding (e.g., Erkutlu & Chafra, 2015;Song, Yu, Zhang, & Jiang, 2015). In a post hoc analysis, though, we found that gender did significantly impact CRI once departmental membership was taken into account, as different departments involved different degrees of creativity in their job roles (Karwowski & Lebuda, 2017 (Haines et al, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 61%
“…Our results support this approach, especially in regard to the robustness of our hypothesized effects while controlling for CRI that would be expected to align with gender role identity. However, it is also noteworthy that CRI did not significantly correlate with gender in our sample, a curious but not unprecedented finding (e.g., Erkutlu & Chafra, 2015;Song, Yu, Zhang, & Jiang, 2015). In a post hoc analysis, though, we found that gender did significantly impact CRI once departmental membership was taken into account, as different departments involved different degrees of creativity in their job roles (Karwowski & Lebuda, 2017 (Haines et al, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 61%
“…Increasing the service quality enhances customer satisfaction, which ultimately retains valued clientele. This effect of service quality has been found for retail banking (Krishnamurthy, SivaKumar, & Sellamuthu, 2010; Mittal & Gera, 2012), the restaurant industry (Qin & Prybutok, 2008; Tam, 2004), lodging industry (Olorunniwo, Hsu, & Udo, 2006), and in telecommunications companies (Song, Lee, & Lee, 2013).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 76%
“…Researchers (e.g. Huang, Huang & Chang, 2019; Song, Yu, Zhang & Jiang, 2015) continue to explore goal orientation in the workplace. Future research should continue to tease out the full impact of goal orientation in multilevel organisational contexts.…”
mentioning
confidence: 99%